Mapping geomorphosites: an analysis of geotourist maps - Bissig, Géraldine (Geotourism/Geoturystyka, 2018)
Within the current research on geomorphosites, the field of mapping is relatively little developed. Studies offering specific mapping methods for geomorphosites are still rare. However, we can observe an important production of maps used for tourism means: “geotourist maps”. This study focuses on such maps. The statistical analysis of fifty or so geotourist maps has allowed us to group them into five categories. This article will discuss the statistical method used (hierarchical cluster analysis) as well as the results obtained. The maps are described according to their graphic components and study of their use illustrates their shortcomings in terms of the transfer of geoscience information. In conclusion, we offer some possibilities for the improvement of geomorphosite mapping for tourist use.//Kartowanie geoobiektów jest dziedziną względnie zacofaną w stosunku do innych aspektów ich badań. Rzadko ukazują się prace poświęcone specyficznym metodom kartowania tych obiektów, natomiast na rynku pojawia się coraz więcej map „geoturystycznych”. Niniejszy artykuł poświęcony jest właśnie temu typowi map. Pokazano zastosowanie hierarchicznej analizy klastrowej do analizy statystycznej około pięćdziesięciu map geoturystycznych, co pozwoliło na wyróżnienie pięciu typów tych map. Zostały one opisane z punktu widzenia składników graficznych i zastosowania. Wykazano ograniczenia w sposobie przekazywania informacji z zakresu nauk o Ziemi. We wnioskach zaproponowano usprawnienie kartowania geoobiektów dla celów turystycznych.